Failure Risks at the Bashtapia Castle Due to Fluctuations in Tigris River Levels - Al-Rahal, Tareq H.; Ali, Harith E.; Al-Badran, Yasir M. (Engineering, Technology & Applied Science Research, 2025)
The current study investigates the stability of Bashtapia Castle (BC) in Mosul, northern Iraq, using two different methodological approaches. The first approach was applied during the early stages of the castle construction, before the Tigris River (TR) reaches the site. The second approach involves assessing the castle's stability under changing levels of the TR. These assessments focus on the stability of the castle trench slopes using Geo-Studio finite element software. The evaluation criteria were based on historical studies and field investigations. Unsaturated strength properties for ditch slope materials beneath the castle structure were obtained and incorporated into the Geo-Studio analysis, including water retention curves, hydraulic conductivity, modulus of elasticity, cohesion, and internal friction angle. The results indicate that the castle construction slightly decreased both the Factor of Safety (FoS) and the shear resistance of the trench slope. Meanwhile, the contact between the TR and the trench slope materials increased the Pore Water Pressure (PWP) and settlement, leading to a reduction in the FOS and shear resistance of these materials.